E-learning assisted AIR learning model to improve students' critical thinking skills - Nanda Safarati; Fatma Zuhra (Jurnal Inovasi Teknologi Pendidikan, 2023)
A learning innovation that combines innovative learning with online learning needs to be done to bridge pandemic conditions such as Covid-19. One of them is the e-learning-assisted AIR learning model (e-AIR). The integration of e-learning into the AIR learning model is carried out to provide learning facilities for students so they can repeat learning material anytime and anywhere. One of the competencies expected to develop in physics courses is CBC. Developing critical thinking is crucial because it is a skill most students need when facing a problem. This study aimed to determine the increase in student CBC by applying the e-learning-assisted AIR learning model for the Physics Education Study Program students at Almuslim University. This quasi-experimental study with a one-group pretest and posttest design was conducted on all Physics Education students at Almuslim University with a sample of 9 students. The research instrument used was in the form of questions adapted to the KBK indicators. Data analysis using the n-gain test. The results of this study show that the e-learning-assisted AIR learning model can improve student CBC, as seen from the percentage obtained, namely as many as five students obtained a percentage of 56%, as many as three students obtained a percentage of 33% in the medium category. As many as one student received 11%, with a low category.